Transformative potential of generative AI in higher education teaching practices - Charisma S. Ututalum (Environment and Social Psychology, 2025)
This study examines the generative potential of AI in reshaping teaching in higher education as related to teaching methods and changing the nature of student involvement. The purpose of the study is to identify ways college educators perceive the roles of Generative AI within their classrooms and to critically evaluate both the benefits and drawbacks of its integration into courses. This adopted qualitative research design, a series of semi-structured interviews of 12 college instructors. The data were analyzed with the help of reflexive thematic analysis to identify important patterns and themes in responses. The findings suggest huge potential for Generative AI in supporting personalization of learning, providing students with tailored experiences in learning. Furthermore, it appears to be enhancing student engagement in learning by creating more interactive learning environments. Further, it can help in reducing the administrative burden on educators since repetitive tasks would be relieved and allow educators more time for meaningful interaction with students. However, the report points out some challenges for its implementation. These range from ethical issues regarding how AI affects academic integrity and personal privacy, proper education and training of teachers who use AI tools, as well as overreliance of students on technology-the likely outcome is impeded ability of students to develop new skills. The best strategy would be adopting the hybrid model, bringing the traditional methods of instruction along with Generative AI.